(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The adoption of digital technologies has significantly altered the landscape of the commerce sector, especially for Small and Medium Enterprises (SMEs). This paper examines how digital transformation impacts SMEs’ performance and sustainability. Using a mixed methods approach, this research identifies key enablers, barriers, and outcomes of digital adoption in commerce. The findings suggest that while digital tools enhance operational efficiency and market reach, challenges such as cost, technical expertise, and infrastructure remain significant. Implications for policymakers and SMEs are discussed to foster a sustainable digital ecosystem.